1995
DOI: 10.1016/s0006-3495(95)80284-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced volume change and energy storage associated with the early transformations of the photoactive yellow protein from Ectothiorhodospira halophila

Abstract: The photocycle of the photoactive yellow protein (PYP) isolated from Ectothiorhodospira halophila was analyzed by flash photolysis with absorption detection at low excitation photon densities and by temperature-dependent laser-induced optoacoustic spectroscopy (LIOAS). The quantum yield for the bleaching recovery of PYP, assumed to be identical to that for the phototransformation of PYP (pG), to the red-shifted intermediate, pR, was phi R = 0.35 +/- 0.05, much lower than the value of 0.64 reported in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
103
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 44 publications
11
103
3
Order By: Relevance
“…4 (perpendicular plane). The momentum carried by the twisted state along the reaction coordinate is conserved better in the protein than in the isolated system because of the ultrashort interaction time in the CI region, and therefore more cis isomers can be formed with high reaction quantum yield (0.24-0.64) (8,11,28,29). That is a critical design by the protein environment to enhance trans-to-cis isomerization in the PYP photocycle.…”
Section: Resultsmentioning
confidence: 99%
“…4 (perpendicular plane). The momentum carried by the twisted state along the reaction coordinate is conserved better in the protein than in the isolated system because of the ultrashort interaction time in the CI region, and therefore more cis isomers can be formed with high reaction quantum yield (0.24-0.64) (8,11,28,29). That is a critical design by the protein environment to enhance trans-to-cis isomerization in the PYP photocycle.…”
Section: Resultsmentioning
confidence: 99%
“…Photoactivity was first reported by Meyer et al (1987), and continuing kinetics analysis has shown that the photocycle is remarkably similar to the bacterial rhodopsins from Halobacterium halobium and related species (Meyer et al, , 1991Hoff et al, 1992;Miller et al, 1993;Ng et al, 1995;Van Brederode et al, 1995). PYP is partially bleached and redshifted from 446 to 465 nm in less than 1 ns, and then it is completely bleached and blue-shifted to 356 nm in 100 µs and finally returns to ground state in 260 ms.…”
mentioning
confidence: 85%
“…The factor 2.303 results from the conversion of the naperian to the decadie absorption coefficient. O4,m equals 0.35 [25], 8446 is 4550 m 2 mo1-1 [26] and 144~, as determined with a quantum sensor, is ,,~3.0× 10 -4 mol photons m -2 s -t. Consequently, kl equals 1.1 s -1. The rate constant k2, referring to the rate of pG recovery, was determined to be 0.05 s -1 at pH 4 [16].…”
Section: The Isomeric State Of L-coumaric Acid In the Blue-shifted Pmentioning
confidence: 99%